Vida Tank Mixtures for Postemergence Weed Control in Fallow - R. S. Currie; P. W. Geier (Kansas Agricultural Experiment Station Research Reports, 2020)
The objective of the study was to compare Vida (pyraflufen ethyl) with various tank mix partners for weed control in fallow. All herbicides controlled flixweed and tansymustard 96% or more by 16 days after treatment. Treatments containing Spartan provided faster and better kochia control compared to other herbicides, and these treatments were the only ones to control kochia 95% or more late in the season.
Keywords: herbicide resistance